Tourisme de l’ordinaire et mise en ordre des espaces et des pratiques ? Réflexion à partir du cas des quartiers nord de Marseille - Isabelle Lefort; Yannick Hascoët (Bulletin de l’Association de Géographes Français)
The transition from « common » to ordinary emphasizes trends in terms of space and chronology but also in terms of social values. This change of status also shows the ackowledgement and the promotion of what makes the contemporary and singular aspects of the individuals, as well as their subjectivities. The field of tourism and heritage practices is raising a lot of questions since it is increasingly characterized by proposals that aim at discovering what makes everyone’s ordinary. But what can be really called ’’ordinary’’? By whom and to what extent are the objects and places that are targeted and visited considered as ordinary? Answering these questions is the purpose of the article, on the bases of previous PhD researches and present studies and investigations of what is called tourism of the ordinary - the Northern districts of Marseille.